Comparison of 111In-[DTPA0]Octreotide Versus Non Carrier Added 177Lu- [DOTA0, Tyr3]-Octreotate Efficacy in Patients With GEP-NET Treated Intra-arterially for Liver Metastases. (March 2016) - Limouris, G. S.; Poulantzas, V.; Trompoukis, N.; Karfis, I.; Chondrogiannis, S.; Triantafyllou, N.; Gennimata, V.; Moulopoulou, L.-E.; Patsouris, E.; Nikou, G.; Michalaki, V.; Fragulidis, G.; et al.
Abstract : Aim: In patients with progressive, metastatic neuroendocrine tumors (NET), intra-arterial radionuclide infusions with high activities of 111 In-[DTPA 0 ]-octreotide and more recently with non-carrier added (nca) 177 Lu-[DOTA 0, Tyr 3 ]-octreotate have been performed with encouraging results. However, the affinity profiles (IC50) of these radiopeptides for human sst2 receptors are markedly different ( 111 In-[DTPA 0 ]-octreotide, 22 ± 3.6 nM and nca 177 Lu-[DOTA 0, Tyr 3 ]-octreotate, 1.5 ± 4.0 nM). The total administered activity is determined by organ dose limits (kidneys and bone marrow), and our aim therefore was to compare and evaluate the therapeutic efficacy of both radiopeptides in metastatic NETs. Methods: Thirty patients with gastroenteropancreatic (GEP) somatostatin-positive NETs with liver metastases confirmed on biopsy and 111 In-pentetreotide scan were included. They were treated with 111 In-[DTPA 0 ]-octreotide (n = 17) or nca 177 Lu-[DOTA 0, Tyr 3 ]-octreotate (n = 13). Blood samples were collected 2, 4, 8, and 24 hours postadministration to calculate residence time in blood and in red marrow. The maximum percentage uptake in organs and tumors was estimated by region of interest analysis, and tumor dosimetry calculations were performed using OLINDA/EXM/ 1.0 software. Results: nca 177 Lu-[DOTA 0, Tyr3]-octreotate blood radioactivity, expressed as a percentage of the injected dose, was significantly lower than 111 In-[DTPA 0 ]-octreotide ( P < 0.05), as clearly depicted from the time-activity curves; the background-corrected tumor uptake was significantly higher than 111 In-[DTPA 0 ]-octreotide but without any significant difference in other organs (spleen, kidneys, and liver). Conclusions: Using 177 Lu-[DOTA 0, Tyr 3 ]-octreotate, a 3-fold higher absorbed dose to tumor tissue was achieved compared with 111 In-[DTPA 0 ] octreotide. Residence time of nca 177 Lu-[DOTA 0, Tyr 3 ]-octreotate results in a significantly higher absorbed dose to bone marrow compared with 111 In-[DTPA 0 ]-octreotide. However, a drawback of 111 In-[DTPA 0 ]-octreotide therapy is that the number of administrations would need to be almost doubled to achieve an equal therapeutic outcome as compared with 177 Lu-[DOTA 0, Tyr 3 ]-octreotate.